Environmental aspects of reforestation and afforestation in northern Kyrgyzstan (Experimental biology, 2015)
There is considering a new method to promote natural regeneration of firtienshan in the squares traversed felling. Proposes the establishment of mixed stands by sowing seeds of disappearing in the region of the local kind of birch. The establishment of such plantings of birch and fir trees the negative effects of cuttings for the environment will be minimal.Protection and the creation of sustainable forest ecosystems as an essential component of the environment, to ensure the stability of values such as water resources and conservation of biodiversity in North Kyrgyzstan, as well as improving the microclimate and climate. Therefore, the right science-based approach to forest management in the region currently is paramount
Keywords: biodiversity conservation; improving microclimate; protection; natural regeneration; establishment of plantings; plantations; environment